Clinical Pattern and Course of Nephrotic Syndrome in Children: An Observational Study - Rahul Kadam; Vidya Singaravelu; Sushama S bai; Madhusudhan (JCDR Research and Publications Pvt. Ltd., 2021)
Introduction: Chronic renal diseases not only affects the personal life of an individual but also results in social and financial burden on their families too. Nephrotic syndrome is most common in the paediatric age group contributing to significant illness related morbidity and even mortality if not identified early and treated promptly. This common disease has shown varying clinical trends with studies attempting to document them. Aim: To study the clinical pattern and course of nephrotic syndrome in children. Materials and Methods: The study was a retrospective analysis of medical records of diagnosed nephrotic syndrome patients in the Paediatrics and Nephrology Departments of a Tertiary Care Medical college hospital. The patients were prospectively followed-up for a period of two years. A total of 90 patients were enrolled into the study and their case records were systematically reviewed to obtain the details regarding age, sex distribution, number of admissions, hospital stay during first admission, complications and interim problems, histopathology finding where indicated, diagnostic classifications based on traditional operational definitions, treatment received, duration of remission after first episode and its relation to future relapses and the final outcome were noted and then statistically analysed. Results: Of the 90 cases of nephrotic syndrome, 14 were lost during follow-up, so remaining 76 patients were included. There were 49 males (64.5%) and 27 females (35.5%). SteroidSensitive Nephrotic Syndrome (SSNS) was the most common type (59%). It was found that 67 (88.1%) patients had first episode within 1-5 years of age, 31(40.8%) had only 1st time admission, 35 (46%) had 2-4 times admissions, while the rest (13.2%) required more than 4 times admissions. Majority of the cases {48 (63.2%)} had hospital stay between 7-14 days. Infectious complications were the most common (35.3%) and 48 (63.1%) cases showed frequent relapse, while 16 (21%) never had a relapse. The final outcome showed 64 (84.2%) of the cases were in remission, 12 (15.8%) were still relapsing, and there was no mortality. Conclusion: Age of onset for nephrotic syndrome was 5 years in majority of cases. Males were more affected than females. Majority of the patients had hospital stay for 7-14 days. SSNS was the most common type of nephrotic syndrome and Urinary Tract Infection (UTI) was the most common infectious complication. As respiratory and UTIs account for majority of relapses, prevention of respiratory infections by observing respiratory etiquettes, early and aggressive treatment and respiratory protective vaccines will go a long way in prevention of relapses.